Analysis of Road Infrastructure Condition Based on Traffic Density in Bengkulu City - Sugeng Pujiyono; Laksono Djoko Nugroho; Haris Muhammadun (Transpublika Publisher, 2025)
The purpose of this research is to explain the analysis of road infrastructure conditions, in terms of traffic density and road quality in Bengkulu City. The research method uses descriptive with qualitative approach, Research Subjects, are people and government institutions, key informants are all people or officials related to road infrastructure policy makers, traffic density and road quality, such as traffic police, transportation department, PUPR department, BPS Bengkulu City. Informants are people or government institutions/institutions that are the object of research, the number is determined based on the criteria of this research. in the form of structured questions for interviews to Informants, Key informants and Triangulation of data. Data Collection Techniques present the sampling methods and data collection techniques used, such as field surveys, direct observation, or the use of secondary data. The results of the analysis using Neil S. Grigg's Infrastructure Management theory state that the condition of Road Infrastructure in Bengkulu City is good based on the criteria of the transport system (roads and bridges), clean water and sanitation systems and energy and other public facilities.